Temperature‐Related Effects on Disease Susceptibility and Immune Response in Redband Trout ( Oncorhynchus mykiss gairdneri ) Following Challenge With Flavobacterium columnare - Joshua P. Egan; Jie Ma; Veronica L. Myrsell; Zhongqi Chen; Jonathan Masingale; Christopher C. Caudill; Timothy Boyle; Julianna Browning; Shawn R. Narum; Kenneth D. Cain; Paul A. Hohenlohe (Journal of Fish Diseases, 2025)
Heat stress can increase disease risk in fishes by reducing immune function. Interactions between redband trout ( Oncorhynchus mykiss gairdneri ) and Flavobacterium columnare , a causative agent of columnaris disease, provide an opportunity to investigate the effects of temperature on immune function and disease resistance during periods of thermal stress. We conducted three trials to characterise differences in immune function and mortality between redband trout held at 18°C and 21°C following challenge with F . columnare . In trial 1, cumulative per cent mortality (CPM) was low and not statistically different between 18°C and 21°C. In trials 2 and 2, we administered higher challenge doses and observed increased CPM overall and significantly greater CPM at 21°C than 18°C. Redband trout upregulated il‐8 , tnf‐α , igm and igt following infection by F . columnare , suggesting that all of these genes may be involved in immune responses to F . columnare infection. We found no differences in the strength of the immune responses between fish held at 21°C versus 18°C. This indicated that 21°C did not elicit sufficient thermal stress to impair immune function and that increased CPM at 21°C versus 18°C was due to enhanced F . columnare virulence.

Extractability indices for screening coal combustion byproduct feedstocks for recovery of rare earth elements - Ward Burgess; Cheuk Fai Chiu; Timothy Cain; Elliot Roth; Murphy Keller; Evan Granite (International Journal of Coal Geology, 2024)

Emergent role of critical interfaces in the dynamics of intensively managed landscapes - Praveen Kumar; Alison Anders; Erin Bauer; Neal E. Blair; Molly Cain; Ashlee Dere; Jennifer Druhan; Timothy Filley; Christos Giannopoulos; Allison E. Goodwell; David Grimley; Diana Karwan; et al. (Earth-Science Reviews, 2023)

Development of a monoclonal antibody specific to burbot (Lota lota) IgM and optimization of an ELISA to measure anti-Aeromonas sp. antibody titers following pathogen challenge - Luke P. Oliver; Timothy J. Bruce; Jie Ma; Evan M. Jones; Kenneth D. Cain (Fish & Shellfish Immunology, 2023)

Characterization of maternal immunity following vaccination of broodstock against IHNV or Flavobacterium psychrophilum in rainbow trout (Oncorhynchus mykiss) - Jie Ma; Jesse T. Trushenski; Evan M. Jones; Timothy J. Bruce; Doug G. McKenney; Gael Kurath; Kenneth D. Cain (Fish & Shellfish Immunology, 2023)

Quantification and comparison of gene expression associated with iron regulation and metabolism in a virulent and attenuated strain of Flavobacterium psychrophilum - Timothy J. Bruce; Jie Ma; Ponnerassery S. Sudheesh; Kenneth D. Cain (Journal of Fish Diseases, 2021)
Iron is essential for growth and virulence in most pathogenic bacterial strains. In some cases, the hosts for these pathogenic bacteria develop specialized strategies to sequester iron and limit infectivity. This in turn may result in the invading pathogens utilizing high‐affinity iron transport mechanisms, such as the use of iron‐chelating siderophores, to extend beyond the host defences. Flavobacterium psychrophilum , the causative agent of bacterial coldwater disease (BCWD) in salmonids, relies on iron metabolism for infectivity, and the genome of the model CSF‐259‐93 strain has recently been made available. Further, this strain serves as a parent strain for a live‐attenuated vaccine strain, B.17, which has been shown to provide rainbow trout with protection against BCWD. To elucidate specific gene expression responses to iron metabolism and compare strain differences, both F. psychrophilum strains were grown under iron‐limiting conditions and 26 genes related to iron metabolism were mapped for 96 hr in culture via qPCR analyses. Results indicate increased production of the ferrous iron transport protein B (FITB; p =.008), and ferric receptor CfrA (FR 1; p =.012) in the wild‐type CSF‐259‐93 strain at 72 hr and 96 hr post‐exposure to iron‐limiting media. In the B.17 vaccine strain, siderophore synthase ( SS ) expression was found to be downregulated at 72 hr, in comparison with 0h ( p =.018). When strains were compared, FITB ( p =.021), FR1 ( p =.009) and SS ( p =.016) were also elevated in B.17 at 0 hr and TonB outer protein membrane receptor 1 (TBomr1; p =.005) had a lower expression at 96 hr. Overall, this study demonstrated strain‐related gene expression changes in only a fraction of the iron metabolism genes tested; however, results provide insight on potential virulence mechanisms and clarification on iron‐related gene expression for F. psychrophilum .

Assessment of Flavobacterium psychrophilum ‐associated mortality in Atlantic salmon ( Salmo salar ) and brook trout ( Salvelinus fontinalis ) - Timothy J. Bruce; Jie Ma; Evan M. Jones; Brent M. Vuglar; Luke P. Oliver; Christopher Knupp; Thomas P. Loch; Kenneth D. Cain (Journal of Fish Diseases, 2021)
Salmonid diseases caused by infections of Flavobacterium psychrophilum , the causative agent of bacterial coldwater disease, remain difficult to manage as novel, pathogenic strains continue to emerge in aquaculture settings globally. To date, much of the research regarding treatment options and vaccine development has focused on rainbow trout ( Oncorhynchus mykiss ), but other inland‐reared salmonids are also impacted by this Gram‐negative bacterium. As such, Atlantic salmon ( Salmo salar ) and brook trout ( Salvelinus fontinalis ) were injection‐challenged with a variety of previously reported F. psychrophilum strains isolated from disease diagnostic cases in salmonids, as well as a standard and well‐studied F. psychrophilum strain (CSF 259–93) known to be virulent in rainbow trout. In three separate virulence assessments (Trials A, B and C), strains US063 (isolated from lake trout; Salvelinus namaycush ) and US149 (isolated from Atlantic salmon) caused a significantly higher cumulative per cent mortality (CPM) relative to other strains in Atlantic salmon ( p p =.008) and B (CPM 96% ± 2.3% vs. 81.33% ± 4.8%, p =.014). Trial C used a lower dose (1.86 × 10 8 CFU/mL) for US149, resulting in a lower mortality (78.67% ± 9.33%) relative to Trials A and B. CSF259‐93 did not cause significant mortality in any trials. In brook trout, the strain 03–179 (originally isolated from steelhead trout; Oncorhynchus mykiss ) was significantly more virulent than any other (CPM 100% ± 0%, p F. psychrophilum virulence testing in Atlantic salmon and brook trout, demonstrating the high virulence of US063 and US149 for these salmonid species. This information is applicable for the development of therapeutics and vaccines against F . psychrophilum infections and demonstrates the reproducibility of the experimental challenge model.

Cross‐protection of a live‐attenuated Flavobacterium psychrophilum immersion vaccine against novel Flavobacterium spp. and Chryseobacterium spp. strains - Timothy J. Bruce; Jie Ma; Christopher Knupp; Thomas P. Loch; Mohamed Faisal; Kenneth D. Cain (Journal of Fish Diseases, 2020)
For salmonid producers, a common threat is Flavobacterium psychrophilum . Recent advancements in bacterial coldwater disease (BCWD) management include the development of a live‐attenuated immersion vaccine that cross‐protects against an array of F. psychrophilum strains. Emerging family Flavobacteriaceae cases associated with clinical disease have been increasing, including pathogenic isolates of Flavobacterium spp. and Chryseobacterium spp. The cross‐protective ability of a live‐attenuated F. psychrophilum vaccine was determined against three virulent Flavobacteriaceae isolates. Juvenile rainbow trout were vaccinated, developed high F. psychrophilum ‐specific antibody titres and were challenged with Chryseobacterium spp. isolates (S25 and T28), a Flavobacterium sp. (S21) isolate, a mixed combination of S21:S25:T28, and a standard virulent F. psychrophilum CSF259‐93 strain. Results demonstrated strong protection in the CSF259‐93 vaccinated group (relative per cent survival (RPS)=94.44%) when compared to the relevant CSF259‐93 controls ( p p

Isolation and experimental challenge of cultured burbot ( Lota lota maculosa ) with Flavobacterium columnare and Aeromonas sp. isolates - Timothy J. Bruce; Jie Ma; Luke P. Oliver; Evan M. Jones; Benjamin R. LaFrentz; Kenneth D. Cain (Journal of Fish Diseases, 2020)
Burbot ( Lota lota maculosa ) are a potential new species for commercial aquaculture. As burbot culture expands, there is a need to further define pathogen susceptibility and characterize aspects of the burbot immune response in an effort to assess fish health. A recent clinical diagnostic case from juvenile burbot reared at a commercial production facility resulted in the isolation and identification of Flavobacterium columnare along with several Aeromonas spp. The F. columnare isolate was assigned to genetic group 1 via multiplex PCR, a genetic group commonly associated with columnaris disease cases in rainbow trout ( Oncorhynchus mykiss ). Virulence of the F. columnare isolate was assessed in vivo in both juvenile burbot and rainbow trout. Additionally, several of the Aeromonas sp. case isolates were identified via sequencing (16S rRNA, gyrB and rpoD ) and a putative A . sobria isolate (BI‐3) was used to challenge burbot, along with a known virulent Aeromonas sp. (A141), but BI‐3 was not found to be virulent. Burbot were refractory to F. columnare when challenged by immersion, and it is likely that this is a secondary pathogen for burbot. Although refractory in burbot, the identified F. columnare isolate (BI‐1) was found to be virulent in rainbow trout.

Co‐infection of rainbow trout ( Oncorhynchus mykiss ) with infectious hematopoietic necrosis virus and Flavobacterium psychrophilum - Jie Ma; Timothy J. Bruce; Luke P. Oliver; Kenneth D. Cain (Journal of Fish Diseases, 2019)
Co‐infection of rainbow trout with infections haematopoietic necrosis virus (IHNV) and Flavobacterium psychrophilum is known to occur, and it has been speculated that a combined infection can result in dramatic losses. Both pathogens can persist in fish in an asymptomatic carrier state, but the impact of co‐infection has not been well characterized or documented. In this study, it was hypothesized that fish co‐infected with F. psychrophilum and IHNV would exhibit greater mortality than fish infected with either pathogen alone. To test this, juvenile rainbow trout were co‐infected with low doses of either IHNV or F. psychrophilum , and at 2 days post‐initial challenge, they were given a low dose of the reciprocal pathogen. This combined infection caused high mortality (76.2%–100%), while mortality from a single pathogen infection with the same respective dose was low (5%–20%). The onset of mortality was earlier in the co‐infected group (3–4 days) when compared with fish infected with F. psychrophilum alone (6 days) or IHNV (5 days), confirming the synergistic interaction between both pathogens. Co‐infection led to a significant increase in the number of F. psychrophilum colony‐forming units and IHNV plaque‐forming units within tissues. This finding confirms that when present together in co‐infected fish, both pathogens are more efficiently recovered from tissues. Furthermore, pathogen genes were significantly increased in co‐infected groups, which parallel the findings of increased systemic pathogen load. Extensive tissue necrosis and abundant pathogen present intracellularly and extracellularly in haematopoietic tissue. This was pronounced in co‐infected fish and likely contributed to the exacerbated clinical signs and higher mortality. This study provides novel insight into host–pathogen interactions related to co‐infection by aquatic bacterial and viral pathogens and supports our hypothesis. Such findings confirm that mortality in fish exposed to both pathogens is greatly elevated compared to a single pathogen infection.

Front Cover - Jie Ma; Timothy J. Bruce; Ponnerassery S. Sudheesh; Christopher Knupp; Thomas P. Loch; Mohamed Faisal; Kenneth D. Cain (Journal of Fish Diseases, 2019)

Assessment of cross‐protection to heterologous strains of Flavobacterium psychrophilum following vaccination with a live‐attenuated coldwater disease immersion vaccine - Jie Ma; Timothy J. Bruce; Ponnerassery S. Sudheesh; Christopher Knupp; Thomas P. Loch; Mohamed Faisal; Kenneth D. Cain (Journal of Fish Diseases, 2019)
Bacterial coldwater disease, caused by Flavobacterium psychrophilum , remains one of the most significant bacterial diseases of salmonids worldwide. A previously developed and reported live‐attenuated immersion vaccine ( F. psychrophilum ; B.17‐ ILM ) has been shown to confer significant protection to salmonids. To further characterize this vaccine, a series of experiments were carried out to determine the cross‐protective efficacy of this B.17‐ ILM vaccine against 9 F. psychrophilum isolates (representing seven sequence types/three clonal complexes as determined by multilocus sequence typing) in comparison with a wild‐type virulent strain, CSF ‐259‐93. To assess protection, 28‐day experimental challenges of rainbow trout ( Oncorhynchus mykiss ) fry were conducted following immersion vaccinations with the B.17‐ ILM vaccine. F. psychrophilum strains used in challenge trials were isolated from several fish species across the globe; however, all were found to be virulent in rainbow trout. The B.17‐ ILM vaccine provided significant protection against all strains, with relative percent survival values ranging from 51% to 72%. All vaccinated fish developed an adaptive immune response (as measured by F. psychrophilum‐ specific antibodies) that increased out to the time of challenge (8 weeks postimmunization). Previous studies have confirmed that antibody plays an important role in protection against F. psychrophilum challenge; therefore, specific antibodies to the B.17‐ ILM vaccine strain appear to contribute to the cross‐protection observed to heterologous strain. The ability of such antibodies to bind to similar antigenic regions for all strains was confirmed by western blot analyses. Results presented here support the practical application of this live‐attenuated vaccine, and suggest that it will be efficacious even in aquaculture operations affected by diverse strains of F. psychrophilum .

Development of community of practice to support quantitative risk assessment for synthetic biology products: contaminant bioremediation and invasive carp control as cases - Benjamin D. Trump; Christy Foran; Taylor Rycroft; Matthew D. Wood; Nirzwan Bandolin; Mariana Cains; Timothy Cary; Fiona Crocker; Nicholas A. Friedenberg; Patrick Gurian; Kerry Hamilton; Jan Jeffrey Hoover; et al. (Environment Systems and Decisions, 2018)

Aromatic metabolism in the fungi. Growth of Rhodotorula mucilaginosa in p-hydroxybenzoate-limited chemostats and the effect of growth rate on the synthesis of enzymes of the 3-oxoadipate pathway - Timothy J. Huber; John R. Street; Alan T. Bull; Keith A. Cook; Ronald B. Cain (Archives of Microbiology, 1975)